Integration of Christ's Love in Family Discipleship to Overcome Fear of Missing Out (FOMO) in Generation Z - Hendrawan, Ari Yunus; Wenas, Maria Lidya; Gunawan, Gunawan (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2023)
Generation Z (Gen Z) dominates Indonesia’s population, numbering 27.94%. Marked by their love for new technologies and fear of becoming “outdated”, these traits surely have a good impact on their development. However, these traits rise new negative impact: the fear of missing out (FOMO) which can lead to lower level of life satisfaction, psychological distress, and anxiety. Based on these problems, the study focuses on integrating the love of Christ in family discipleship to overcome FOMO in Gen Z.  The authors used qualitative research approach by using literature review. Based on the review of various literature sources and idea framework building, the authors proposed three steps of discipleship in the family according to the love of Christ in overcoming FOMO. Firstly, discipleship is conducted by exposition to agape love concept, which has a role in shaping concept of self in the family environment. Gen Z is discipled by guiding them to receive God's love that provides forgiveness and restoration for sinners. Secondly, discipleship is conducted in family by exposition to storge love concept. Parents provide guidance and education lovingly without having to arouse Gen Z’s anger. Third, discipleship is conducted by exposition to philia love concept, which occurs in an environment of friendship. The family becomes a common place to exhibit Christlikeness in an atmosphere of friendship. Parents become friends to Gen Z and help them experience character and spiritual growth like a friend.Al-Saggaf, Y., & O’Donnell, S. B. (2019). Phubbing: Perceptions, reasons behind, predictors, and impacts. Human Behavior and Emerging Technologies, 1(2), 132–140. https://doi.org/10.1002/hbe2.137Angeline, S., & Ronda, D. (2011). Pemulihan Gambar Diri Bagi Pekerja Seks Komersial Di Pusat Pelayanan Satuan Karya Wanita Mattiro Deceng Makassar. Jurnal Jaffray, 9(2), 31–52. https://doi.org/10.25278/jj71.v9i2.95APJII. (2022). Profil Internet Indonesia 2022. Apji.or.Od, June, 10. apji.or.idAtkinson, R. L., Smith, E. E., Atkinson, R. C., Bem, D. J., & Nolen-Hoeksema, S. (2010). Pengantar Psikologi, Jilid 1. Interaksa.Badan Pusat Statistik Provinsi DKI Jakarta. (2021). Hasil Sensus Penduduk 2020. Sensus Penduduk 2020, 06, 1–12.Berkhof, L., & Til, C. van. (2013). Foundations of Christian Education (kelima). Momentum.Burke, T. J. (2013). The Parable of the Prodigal Father: An Interpretative Key to the Third Gospel (Luke 15:11-32). Tyndale Bulletin, 64(2). https://doi.org/10.53751/001c.29357Chandra, R. (2021). Perjalanan Spiritual Homo Viator: Studi Komparatif Serat Jatimurti dengan Perumpamaan tentang Anak yang Hilang (Luk. 15:11–32). Veritas: Jurnal Teologi Dan Pelayanan, 20(1), 107–124. https://doi.org/10.36421/veritas.v20i1.465Chotpitayasunondh, V., & Douglas, K. M. (2016). How ‘phubbing’ becomes the norm: The antecedents and consequences of snubbing via smartphone. Computers in Human Behavior, 63, 9–18. https://doi.org/10.1016/j.chb.2016.05.018Darmalaksana, W., Aziz, W. D. I., Rahmatullah, S., Irwansyah, F. S., Sugilar, H., Maylawati, D. S., & Suhendi, H. Y. (2018). Analisis Ranking Produktivitas Publikasi Ilmiah Berbasis h-Index Google Scholar. http://digilib.uinsgd.ac.id/5722/Darmawan, I. P. A., & Objantoro, E. (2020). Signifikansi Ineransi Alkitab Bagi Pendidikan Kristen. Sola Scriptura: Jurnal Teologi, 1(1), 36–52. https://journal.sttjohanescalvin.ac.id/index.php/Scriptura/article/view/34Diana, R. (2019). Prinsip Teologi Kristen Pendidikan Orang tua terhadap Anak di Era Revolusi Industri 4.0. BIA’: Jurnal Teologi Dan Pendidikan Kristen Kontekstual, 2(1), 27–39. https://doi.org/10.34307/b.v2i1.79Ellithorpe, A.-M. (2022). Towards friendship-shaped communities: a practical theology of friendship. Wiley-Blackwell. https://www.wiley.com/en-us/Towards+Friendship+Shaped+Communities%3A+A+Practical+Theology+of+Friendship-p-9781119756965Frazee, R., & Noland, R. (2016). Berpikir, Bertindak, Menjadi Seperti Yesus. Katalis.Gaskin, J. A. (2023). Role of Forgiveness in The Grief Process for Children in Crisis. Evangelikal: Jurnal Teologi Injili Dan Pembinaan Warga Jemaat, 7(1), 13–22. https://doi.org/10.46445/ejti.v7i1.600Gunawan, A. (2020). Pemuridan Dan Kedewasaan Rohani. SOLA GRATIA: Jurnal Teologi Biblika Dan Praktika, 5(1), 1–17. https://doi.org/10.47596/solagratia.v5i1.52Hartono, H. (2018). Membentuk Karakter Kristen Pada Anak Keluarga Kristen. KURIOS (Jurnal Teologi Dan Pendidikan Agama Kristen), 2(1), 62–69. https://doi.org/10.30995/kur.v2i1.22Haryono, T. (2021). Model Pemuridan Berbasis Keluarga Era New Normal Pandemi Covid-19. DUNAMIS: Jurnal Teologi Dan Pendidikan Kristiani, 5(2), 307–324. https://doi.org/10.30648/DUN.V5I2.366Hastuti, R. (2013). Pendidikan Agama Kristen Dalam Keluarga Sebagai Pusat Bermisi. Jurnal Antusias, 2(4). https://www.sttintheos.ac.id/e-journal/index.php/antusias/article/view/23Hayran, C., & Anik, L. (2021). Well-Being and Fear of Missing Out (FOMO) on Digital Content in the Time of COVID-19: A Correlational Analysis among University Students. International Journal of Environmental Research and Public Health, 18(4), 1974. https://doi.org/10.3390/ijerph18041974Henry, M. (1706). Matthew Henry commentary on the whole Bible (complete). Bible Study Tools.Henry, M. (2015). Surat Galatia, Efesus, Filipi, Kolose, 1 & 2 Tesalonika, 1 & 2 Timotius, Titus, Filemon. Momentum.Hoekema, A. A. (2009). Created in God’s Image. Wm. B. Eerdmans.Irawan, H., Yahya, K., Tanbunaan, G. I., Arthanto, H. G., Liang, T. P., Suhendra, J., & Budijanto, B. (2018). Dinamika Spiritualitas Generasi Muda Kristen Indonesia (B. Budijanto (ed.)). Yayasan Bilangan Research Center.Karnawati, K., Hosana, H., & Darmawan, I. P. A. (2019). Lingkungan Proses Pembelajaran Yesus. Veritas Lux Mea (Jurnal Teologi Dan Pendidikan Kristen), 1(2), 76–89. http://jurnal.sttkn.ac.id/index.php/Veritas/article/view/48Karnawati, K., Yahya, N. C. A., & Darmawan, I. P. A. (2020). Tahapan Pembelajaran Yesus pada Perempuan Samaria. Davar?: Jurnal Teologi, 1(1), 9–18. https://doi.org/10.55807/davar.v1i1.4Katarina, K., & Darmawan, I. P. A. (2019). Implikasi Alkitab dalam Formasi Rohani pada Era Reformasi Gereja. EPIGRAPHE: Jurnal Teologi Dan Pelayanan Kristiani, 3(2), 81–93. https://doi.org/10.33991/epigraphe.v3i2.85Kristanti, D., Magdalena, M., Karmiati, R., & Emiyati, A. (2020). Profesionalitas Yesus Dalam Mengajar Tentang Kasih. Didache: Journal of Christian Education, 1(1), 35–48. https://doi.org/10.46445/djce.v1i1.286Mary, E., Udau, S., & Darmawan, I. P. A. (2022). Theological knowledge internalization in man and sin doctrine learning. International Journal of Humanities and Innovation (IJHI), 5(1), 1–7. https://doi.org/10.33750/ijhi.v5i1.130Maysitoh, M., Ifdil, I., & Ardi, Z. (2020). FoMO (Fear of Missing Out) Tendency in Millennials. Journal of Counseling, Education and Society, 1(1), 1–4. https://doi.org/10.29210/08jces44700Ndolu, N. N., Anika Tusi, & Purnomo, C. P. (2020). Studi Penerapan Nilai Kasih Storge Orangtua Terhadap Anak di GMIT Jemaat Syalom Oinlasi. PEADA’?: Jurnal Pendidikan Kristen, 1(2), 72–84. https://doi.org/10.34307/peada.v1i2.16Nggebu, S. (2022). Peran Eksklusif Orang Tua dalam Membentuk Konsep Diri Remaja Kristen. Sola Gratia, 2(2), 130–149. https://doi.org/10.47596/SG.V2I2.154O’Brien, P. T. (1999). The Letter to the Ephesians. William B. Eerdmans Publishing Company.O’Brien, P. T. (2013). Tafsiran Pilihan Momentum?: Surat Efesus (First Edit). Momentum.Oematan, N. S. (2022). Providensia Allah bagi Kebahagiaan Rumah Tangga Kristen. REDOMINATE: Jurnal Teologi Dan Pendidikan Kristiani, 4(1), 67–77. https://sttkerussoindonesia.ac.id/e-journal/index.php/redominate/article/view/37Patty, F. N., Wenno, V. K., & Toisuta, F. A. (2020). Keluarga dan Pendidikan Karakter: Menggali Implikasi Nilai-nilai Hausetafel dalam Efesus 6:1-9. KURIOS (Jurnal Teologi Dan Pendidikan Agama Kristen), 6(2), 202. https://doi.org/10.30995/kur.v6i2.155Prayogo, J. A. (2020). Parenting Anak Remaja Di Era Digital. Prosiding Seminar Nasional Kristen 2020, “Spiritual Growth and Its Challenges For The Christian Life In The Millennial Era”, 32–38.Przybylski, A. K., Murayama, K., DeHaan, C. R., & Gladwell, V. (2013). Motivational, emotional, and behavioral correlates of fear of missing out. Computers in Human Behavior, 29(4), 1841–1848. https://doi.org/10.1016/j.chb.2013.02.014Putri, L. S., Purnama, D. H., & Idi, A. (2019). GAYA HIDUP MAHASISWA PENGGUNA MEDIA SOSIAL DI KOTA PALEMBANG (Studi Pada Mahasiswa FoMO di Universitas Sriwijaya dan Universitas Muhammadiyah Palembang). Jurnal Masyarakat Dan Budaya, 21(2), 129–148. https://doi.org/10.14203/JMB.V21I2.867Rahayuningsih, T., & Sumaryanti, I. U. (2022). Pengaruh Tingkat Neuroticism terhadap Fear of Missing Out (FoMO) pada Mahasiswa Pengguna Instagram. Bandung Conference Series: Psychology  Science, 2(2), 463–471. https://doi.org/10.29313/BCSPS.V2I3.3096Reed, L. A., Tolman, R. M., & Safyer, P. (2015). Too close for comfort: Attachment insecurity and electronic intrusion in college students’ dating relationships. Computers in Human Behavior, 50, 431–438. https://doi.org/10.1016/j.chb.2015.03.050Research Center, B. (2018). Temuan Hasil Survei Spiritualitas Generasi Muda Kristen Indonesia.Rifaya, S. D. J. (2022). The Relationship of Loneliness with Fear of Missing Out in Early Adult TikTok App Users [Universitas 17 Agustus 1945 Surabaya]. In Computers in Human Behavior (Vol. 29, Issue 4). http://repository.untag-sby.ac.id/20115/Roy, B., & Yosef, A. (2019). Pertumbuhan Rohani Anak Dalam Keluarga Kristen Menurut Efesus 6:4. The Way Jurnal Teologi Dan Kependidikan, 5(1), 52–69. https://journal.sttbetheltheway.ac.id/index.php/teologi-dan-kependidikan/article/view/4Santrock, J. (1999). Life Span Development (7th ed.). McGraw-Hill College.Sidjabat, B. S. (2011). Membangun Pribadi Unggul Suatu Pendekatan Teologis Terhadap Pendidikan Karakter. Andi.Sulistyorini, W., & Sabarisman, M. (2017). Depresi?: Suatu Tinjauan Psikologis. Jurnal Sosio Informa, 3(2), 153–164. https://doi.org/10.33007/inf.v3i2.939Susanti, M. R. (2020). Studi Biblika 1 Yohanes 4:19 Tentang Mengasihi Dalam Peningkatan Kepedulian Sesama. FILADELFIA: Jurnal Teologi Dan Pendidikan Kristen, 1(2), 106–119. https://doi.org/10.55772/filadelfia.v1i2.12Tafona’o, T. (2016). Pendidikan Agama Dalam Masyarakat Majemuk. In Fondasia (2nd ed., Vol. 1, Issue 2). illumiNation Publishing. https://doi.org/10.21831/foundasia.v1i9.5868Tatl?, C., & Ergin, D. A. (2022). Multigroup analysis of the relationship loneliness, fear of missing out, problematic internet usage and peer perception in gifted and normally developing adolescents. Current Psychology. https://doi.org/10.1007/s12144-022-03384-5Trikusuma, G. A. A. C., & Hendriani, W. (2021). Distres Psikologis di Masa Pandemi COVID 19: Sebuah Tinjauan Literatur Sistematis. INSAN Jurnal Psikologi Dan Kesehatan Mental, 6(2), 106–116. https://doi.org/10.20473/jpkm.V6I22021.106-116Waharman, W. (2018). Peran Orang Tua Dalam Pertumbuhan Spritualitas Anak: Sebuah Studi Eksegetis Efesus 6:1-4. Manna Rafflesia, 4(2), 116–129. https://doi.org/10.38091/man_raf.v4i2.92Wei, M., Mallinckrodt, B., Larson, L. M., & Zakalik, R. A. (2005). Adult Attachment, Depressive Symptoms, and Validation From Self Versus Others. Journal of Counseling Psychology, 52(3), 368–377. https://doi.org/10.1037/0022-0167.52.3.368Wesly, D. K., Sujoko, E., & Riniwati, R. (2021). Peran dan Kendala Orang Tua Dalam Pendampingan Pembelajaran Siswa Pendidikan Agama Kristen Dimasa Pandemi Covid-19. Didache: Journal of Christian Education, 2(2), 133–144. https://doi.org/10.46445/djce.v2i2.441Zaluchu, S. E. (2019). Eksegesis Kisah Para Rasul 2:42-47 untuk Merumuskan Ciri Kehidupan Rohani Jemaat Mula-mula di Yerusalem. EPIGRAPHE: Jurnal Teologi Dan Pelayanan Kristiani, 2(2), 72–82. https://doi.org/10.33991/epigraphe.v2i2.37Zaluchu, S. E. (2021). Metode Penelitian di dalam Manuskrip Jurnal Ilmiah Keagamaan. Jurnal Teologi Berita Hidup, 3(2), 249–266. https://doi.org/10.38189/jtbh.v3i2.93